Body composition and metastatic prostate cancer survivorship. (2021) - Coletta, Adriana M; Sayegh, Nicolas; Agarwal, Neeraj
Highlights: Low muscle mass is linked with increased risk of disease progression and mortality. Excess fat mass is linked with increased risk of mortality. Proposed mechanisms include myokines, immune function, and insulin sensitivity. Lifestyle tactics improve body composition in metastatic prostate cancer patients. Abstract: There is a growing body of evidence related to the importance of body composition in cancer survivorship. Current evidence exclusive to the metastatic prostate cancer setting is limited, yet sheds light on the importance of body composition to reduce risk of mortality and disease progression in this patient population. In our commentary we present the current state of evidence related to body composition and metastatic prostate cancer survival among metastatic castration-resistant and castration-sensitive prostate cancer patients among varying treatment modalities. Additionally, we discuss the proposed biological mechanisms that may underpin how favorable changes in body composition may be helpful for survivorship, and review promising lifestyle strategies that can be implemented as part of survivorship care to improve body composition in this patient population.